Improving Blasting Cleanliness: Integration of Used Transmission Oil in Emulsion Explosive at Indonesia Mine - Khiva Haidar Shauma Tassno; Farhan Harist Maharesi; Zulham Ahmad; Abdullah Badawi Batubara (International Society of Explosives Engineers, 2026)
Blasting operations can use a bulk emulsion explosive (EE) with a formulation based on used oil as a replacement for refined fuel oil. The most commonly employed used oil for making EE is a mineral based used engine oil that passes an impurity content standard. It is known that not all types of used oil are easily incorporated into EE formulations. Impurities in used oil can disturb EE stability resulting in crystallization and phase separation and consequently led to poor detonation quality. In 2024, a poor blast result occurred at an Indonesian mine due to utilization of used oil that was not within specification. A research project conducted from February to April 2025 found that used transmission oil differs from used engine oil in hydrocarbon composition. Transmission oil contains more additives that affect EE stability due to polarity differences and the disruption of colloidal state stability. Lab tests including stress testing and crystal growth observation aided the development of a stable EE formulation based on used oil and used transmission oil. In mid-April 2025, blast evaluations were conducted using the EE that was formulated using used engine oil and used transmission oil. Measurements of velocity of detonation, fragmentation, and digging time, demonstrated high quality EE was produced. Application of used oil in EE revolutionized the capability of mining operations to improve blast sustainability and cleanliness. Through comprehensive research, robust testing, and effective supply chain management, it is possible to replace some portion of refined fuel oil with used oil without compromising blasting performance. The inclusion of used transmission oil broadens the overall used oil specification and increases the volume of recycled used oil available for blasting. The increased volume of used oil available can reduce the amount of waste generated by mining projects while maintaining operational efficiency.